2023
DOI: 10.3390/met13030466
|View full text |Cite
|
Sign up to set email alerts
|

Strength Analysis of Eight-Wheel Bogie of Bucket Wheel Excavator

Abstract: Crawler travel gear is a type of heavy vehicle propulsion that is commonly found in tanks, excavators, and specialized off-road vehicles. They have an advantage over wheels when it comes to robust vehicle weight distribution over soft terrain, and some disadvantages as well. They can damage paved roads and have complex design so, considering the enormous weight they must carry, their reliability must be determined and verified. The main parts of the assembly are the drive wheels, which move the crawler, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Stress analysis revealed that the maximum stress acting on the ring gear and drive shaft was 204.2 MPa. This can confirm reliability by ensuring that it does not break under extreme conditions that will be used in producing the electric wheelchair drive unit [20,21]. The maximum strain appears at the end of the shaft connected through the pulley and key, with a value of 0.064453 mm, which is very small, allowing cross-verification of safety [22].…”
Section: Gear Stress Analysismentioning
confidence: 87%
“…Stress analysis revealed that the maximum stress acting on the ring gear and drive shaft was 204.2 MPa. This can confirm reliability by ensuring that it does not break under extreme conditions that will be used in producing the electric wheelchair drive unit [20,21]. The maximum strain appears at the end of the shaft connected through the pulley and key, with a value of 0.064453 mm, which is very small, allowing cross-verification of safety [22].…”
Section: Gear Stress Analysismentioning
confidence: 87%
“…The collection includes papers regarding the most multifaced aspects of metals and their alloys as synthesis and treatments [1], experimental characterization [2][3][4], material models [2,5,6], and engineering applications [7,8], providing a clear cross-section of the wide variety of topics and research arguments under investigation in the scientific community now.…”
Section: Contributionsmentioning
confidence: 99%
“…The [8] discusses the crawler travel gear, a heavy vehicle propulsion system commonly used in tanks, excavators, and off-road vehicles. Crawler travel gears offer advantages in distributing vehicle weight over soft terrain, but they can also damage paved roads and have complex designs.…”
Section: Contributionsmentioning
confidence: 99%
“…At present, the welding of magnesium alloy is mainly used in engineering fields such as aviation, aerospace, transportation, chemical engineering, and rockets [2]. Therefore, the reliable connection between magnesium and galvanized steel has great potential for manufacturing lightweight structural components, and can also expand the application of magnesium alloys in various fields [3,4]. However, the welding performance of magnesium alloys is relatively insufficient.…”
Section: Introductionmentioning
confidence: 99%